Mapping the Landscape of E-Business Systems: A Bibliometric Review and Future Research Directions - Fatmayati, Fryda; Hanifah Nurul Muthmainah (Eastasouth Institute, 2023)
This research paper presents a comprehensive bibliometric review of the e-business systems landscape, analyzing publication trends, citation patterns, influential authors, and prevalent research themes. E-business systems, driven by technological advancements and changing consumer behaviors, have reshaped modern business practices. Through systematic data collection and analysis, this study reveals the evolution of research within this dynamic field. The findings underscore the interdisciplinary nature of e-business systems, spanning information technology, strategy, marketing, and more. The identification of influential authors, prevalent themes, and emerging directions provides a roadmap for scholars, practitioners, and policymakers to navigate the evolving landscape of e-business systems.